O impacto da conferência de Santiago do Chile de 1923 nas relações Brasil-Argentina - Romeiro, Alfredo Perozo [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Este trabalho analisa os impactos da V Conferência Pan-Americana de Santiago do Chile de 1923 para as relações bilaterais Brasil-Argentina. O objetivo desta monografia é apurar os potenciais danos causados ao entendimento entre esses dois Estados devido a controvérsias ocorridas antes, durante e depois da Conferência em questão. O método utilizado para tal será o estudo e análise bibliográfica da literatura disponível sobre o tema, fazendo uma síntese dos dados existentes a respeito do fenômeno pan-americano e das relações bilaterais Brasil-Argentina com a V Conferência Pan-Americana como principal ponto de intersecção. Os resultados apontam para uma série de grandes reveses para as relações entre os dois Estados, que ocorreram lado a lado, contudo, com importantes gestos de aproximação, cooperação e amizade entre Brasil e Argentina. Conclui-se, portanto, que enquanto de fato o saldo da V Conferência Pan-Americana foi negativo para as relações Brasil-Argentina, os danos dela decorrentes foram limitados, e restritos ao curto prazo.

This monography analyses the impacts of the 5th Pan-American Conference of Santiago de Chile of 1923 for the bilateral relations of Brazil and Argentina. The goal of this monography is to investigate the potential damages caused to the mutual understanding between both countries due to controversies which took place before, during and after the Conference in question. The method employed for this task is the bibliographical study and analysis of the avaliable literature on the topic, formulating a synthesis of the existing data on the pan-american phenomenon and the bilateral relations of Brazil and Argentina, with the 5th Pan-American Conference as the main point of overlap. The results thus obtained point to a series of major setbacks to the relations between those two States, which happened side by side, however, with important gestures of rapproachement, cooperation and friendship between Brazil and Argentina. It is concluded, therefore, that while the balance of the 5th Pan-American Conference was negative for relations between Brazil and Argentina, the damages stemming from it were limited, and restricted to the short term.
The impact of the Santiago de Chile conference of 1923 on Brazil-Argentina relations
Keywords: Conferências pan-americanas; Política externa brasileira; Relações Brasil-Argentina; Pan-american conferences; Brazilian foreign policy; Brazil-Argentina relations